CHALLENGES OF PLANT DISEASE EPIDEMIOLOGY IN WORLD FOOD SECURITY IN THE INDUSTRY 4.0 ERA: TANTANGAN EPIDEMIOLOGI PENYAKIT TANAMAN DALAM KETAHANAN PANGAN DUNIA DI ERA INDUSTRI 4.0 - Manis Baene, Gadis (UPMI Proceeding Series, 2023)
This research is a literature study with a type of descriptive qualitative research with a literature review (Library research) that describes the epidemiological challenges of plant diseases in food security. The author uses various written sources such as articles, journals and documents relevant to the study in this study. This study focuses on the discourse of world food security in the industrial era 4.0. The results of the study show that the model and technological innovation of the Industrial Revolution 4.0 is very important in the agricultural sector where farming will be more efficient so that there is an increase in productivity and competitiveness. The technological innovation of the industrial revolution 4.0 can attract the younger generation to love agriculture more and want to farm in the agricultural sector. The challenges that must be faced in the industrial revolution 4.0 are the need for infrastructure improvements, costs, and farmers who are not yet technologically literate.